2012
DOI: 10.3389/fpsyg.2012.00503
|View full text |Cite
|
Sign up to set email alerts
|

Too Much of a Good Thing: Random Practice Scheduling and Self-Control of Feedback Lead to Unique but Not Additive Learning Benefits

Abstract: We examined the impact of self-controlled knowledge of results on the acquisition, retention, and transfer of anticipation timing skill as a function of random and blocked practice schedules. Forty-eight undergraduate students were divided into experimental groups that practiced under varying combinations of random or blocked as well as self-controlled or yoked practice conditions. Anticipation timing performance (5, 13, and 21 mph) was recorded during acquisition and during a short term no-feedback retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 54 publications
(74 reference statements)
3
13
0
3
Order By: Relevance
“…In the second day trainings, both groups showed a plateau effect, suggesting that the provided information could not support further skill development. This result is interesting because we would have expected from VD group a further progress on the precision based on the previously reported effectiveness of practice variability (Donakowski, 2005) and randomized training (Ali et al, 2012) on the temporal variability. However, these studies investigated artificial laboratory tasks to be learned; thus, conclusions from simple tasks may not extend to the real-life complex tasks (Wulf and Shea, 2002).…”
Section: Velocity Variabilitymentioning
confidence: 69%
“…In the second day trainings, both groups showed a plateau effect, suggesting that the provided information could not support further skill development. This result is interesting because we would have expected from VD group a further progress on the precision based on the previously reported effectiveness of practice variability (Donakowski, 2005) and randomized training (Ali et al, 2012) on the temporal variability. However, these studies investigated artificial laboratory tasks to be learned; thus, conclusions from simple tasks may not extend to the real-life complex tasks (Wulf and Shea, 2002).…”
Section: Velocity Variabilitymentioning
confidence: 69%
“…For top performance accomplishment in sports, the brain dynamics needs to be taken into account because it determines both motor control and crucial psychological factors, such as intrinsic motivation (Pedersen, 2002 ), selective attention (Arjona et al, 2014 ; Abdollahipour et al, 2015 ), goal setting (West and Thorn, 2001 ), working memory (Dipoppa and Gutkin, 2013 ), decision making (Renfree et al, 2014 ), positive self-concept (Badami et al, 2012 ), and self-control (Ali et al, 2012 ; Chiviacowsky et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, many researchers have found that the eff ectiveness of self-controlled feedback varies in accordance with task diffi culty (e.g., simple and complex), subject and task characteristics (e.g., age, open and closed skills), practice conditions (blocked vs. random), forms of knowledge contained in feedback (knowledge of result, knowledge of performance), motivation, ability to process information, and when combined with other learning manipulations ( Yook, Yoon, & Lee, 2005 ;Aiken, et al ., 2012 ;Ali, Fawver, Kim, Fairbrother, & Janelle, 2012 ;Carter, Carlsen, & Ste-Marie, 2014 ). For example, Bund and Wiemeyer (2004 ) investigated whether self-controlled feedback would enhance a complex motor skill learning.…”
mentioning
confidence: 99%